2011
DOI: 10.1001/archoto.2011.4
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Universal Newborn Hearing Screening in Early Identification of Pediatric Cochlear Implant Candidates

Abstract: Almost one-third of our pediatric implant recipients pass UNHS and are older at the time of initial diagnosis and implantation than their peers who fail UNHS. Delayed onset of SNHL limits our ability to achieve early diagnosis and implantation of a significant number of deaf children. This problem will not be solved by the current design of universal hearing screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…In the current study population 20.3% of children presented with a postnatal onset with 8.5% having a late onset progressive hearing loss and 11.8% having sudden hearing loss. ANSD was diagnosed in 5% of the cases which compares to previous reports where the prevalence of ANSD in children ranged from 4.1 to 14% [40,55,56]. For developing countries such as India and Egypt, the reported prevalence ranges are 13.4 to 14% [57,58] and reports available for sub-Saharan Africa suggest an even higher prevalence.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In the current study population 20.3% of children presented with a postnatal onset with 8.5% having a late onset progressive hearing loss and 11.8% having sudden hearing loss. ANSD was diagnosed in 5% of the cases which compares to previous reports where the prevalence of ANSD in children ranged from 4.1 to 14% [40,55,56]. For developing countries such as India and Egypt, the reported prevalence ranges are 13.4 to 14% [57,58] and reports available for sub-Saharan Africa suggest an even higher prevalence.…”
Section: Discussionmentioning
confidence: 50%
“…Within a sample of pediatric cochlear implant recipients, Young et al [40] also reported 9.5% of children presenting with a syndrome.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Young et al 15 reported that one-third of their pediatric cochlear implant recipients had passed the hearing screening at birth. In an earlier study, Johnson et al 7 estimated that ∼23% of infants with hearing loss are missed because they pass the automated ABR screening test; yet, the concerning issue of infants who are missed by the hearing screening has been widely overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Not knowing the etiology may contribute to the stress reported in families after confirmation of hearing loss in their child (Vohr et al 2008). Additionally, not all infants with significant early-onset hearing loss will have positive newborn screens (Young et al 2011), thus preventing early identification. Sequencing could potentially detect mutations in all known syndromic and nonsyndromic hearing loss genes, thus providing a specific diagnosis not only in infants with a genetic cause of hearing loss detected through NBS but also in those who would otherwise not be identified through NBHS and thus provides a method to expand the scope of NBS.…”
Section: Hearing Lossmentioning
confidence: 99%